2005
DOI: 10.1021/mp0498897
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric Ad5 Vectors Expressing the Short Fiber of Ad41 Show Reduced Affinity for Human Intestinal Epithelium

Abstract: Altering adenovirus tropism has attracted increased attention in recent years to improve gene delivery. We constructed a recombinant Ad5 vector carrying the non-CAR (coxsackievirus and adenovirus receptor) binding short fiber of enterotropic Ad41 (Ad5SHORT) and tested its transduction efficiency on enterocytes. Ad5SHORT was engineered, in high titers similar to the parent vector, by homologous recombination in Escherichia coli BJ5183 (recBC sbcBC) and propagated on C7 cells. Western blotting confirmed the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Furthermore, the SF of enteric HAdVs have been suggested to be responsible for the restricted intestinal tropism since these viruses were shown to be more resistant to acidic pH than other HAdV types [29,30]. This claim was refuted by another study describing that a recombinant HAdV-C5 vector carrying the 41SFs showed reduced affinity for enterocytes [57]. The latter study, however, did not subject the virions to acidic pH, which could have affected their results and interpretations.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the SF of enteric HAdVs have been suggested to be responsible for the restricted intestinal tropism since these viruses were shown to be more resistant to acidic pH than other HAdV types [29,30]. This claim was refuted by another study describing that a recombinant HAdV-C5 vector carrying the 41SFs showed reduced affinity for enterocytes [57]. The latter study, however, did not subject the virions to acidic pH, which could have affected their results and interpretations.…”
Section: Discussionmentioning
confidence: 99%
“…However, the incorporation of a 7-lysine-residue motif at the C-terminal end of the Ad40 short fiber in Ad5/40S recovered the transduction efficiencies. The chimeric Ad5SHORT that carries the Ad5 genome and Ad41 short fiber exhibited decreased transduction of human intestinal epithelial cells [148]. Therefore, Ad5/40S and Ad5SHORT are good candidates to employ bispecific conjugates to link the viral capsid and different target cancer cells, while avoiding the transduction of cells expressing the CAR receptor [149].…”
Section: Construction and Evaluation Of Chimeric Oncolytic Adenovirusesmentioning
confidence: 99%
“…In this regard, the generation of chimeric Ad5/40S mutants (Ad5 capsid with the F40S protein) has shown to ablate CAR binding while conferring a novel tropism to Ad5 viral vectors, and thus, intravenous administration of Ad5/40S vectors resulted mainly in liver and spleen transduction, as shown by the presence of viral DNA and transgene expression in these organs, while the virus was hardly detected in the intestine [15]. However, and contrary to the reduced affinity of Ad5/41S vectors for human intestinal epithelium [19], when given directly into the gastrointestinal tract by rectal administration in vivo, chimeric Ad5/40S vectors mantain the enteric tropism [20].…”
Section: Introductionmentioning
confidence: 99%